THE PSYCHOLOGICAL IMPACT OF FLASH FLOODS ON COMMUNITY PSYCHOLOGICAL RESILIENCE - mufidanasution, sitirizka (AGENDA: Jurnal Analisis Gender dan Agama, 2024)
Natural disasters rarely have an impact on the lives of Indonesian people. The response to disasters is still ongoing after disasters such as floods, landslides and volcanic eruptions continue to occur. Tana Datar Regency in West Sumatra Province is currently in a transition period following the flash floods of Mount Marapi and the cold lava flow which claimed dozens of lives some time ago. The disaster is estimated to cause losses of up to IDR 500 billion.Currently Tana Datal has emergency transition status for natural disaster recovery following cold lava floods, flash floods and landslides. The flash floods in West Sumatra in February 2021 left deep wounds for the affected communities. Apart from physical damage, this disaster also had a significant psychological impact. Victims experience trauma, stress, anxiety and depression due to the loss of property, homes and loved ones. Fear and stigma haunt them. Psychological recovery efforts such as trauma healing, psychosocial support, economic empowerment, and disaster preparedness education are the keys to helping communities get back on their feet.  It is important to remember that each individual has different ways of dealing with trauma. Appropriate and professional support and assistance from mental health workers is really needed in this recovery process.